Juvenile Hyaline Fibromatosis - Child with Scalp Swellings - Naila Parveen; Javeria Mansoor; Komal Masroor (Journal of Liaquat National Hospital)
Juvenile hyaline fibromatosis is a recessive autosomal hereditary disorder characterized by abnormal growth of hyalinized fibrous tissue. Its clinical presentation is manifested by benign skin lesions, bone lesions, joint contractures, and gingival hyperplasia. The underlying cause is an abnormal growth of hyalinized fibrous tissue with cutaneous, mucosal, osteoarticular, and systemic involvement. This report presents a case of a 4-year-old male child; with complaints of multiple painful body swellings and pus discharge from scalp swellings for the past two years admitted at Dr. Ruth Pfau Civil Hospital, Karachi, 2021. This patient had right occipital scalp swelling of 10x 10 cm due to which surgery was done and the excision was successful. Other findings included stiff joints, skin overgrowth over the scalp and back + buttocks, multiple firm cystic swellings on the scalp, back, trunk, and whole body involving the face (nose), anal region, gum hypertrophy, and various papules over the nose.